The Mediating Role of Religious Orientation in the Relationship between Cognitive Emotion Regulation Strategies and Corona Anxiety - Sayeed Hossein Tabatabaee; Jamshid Jarareh; Asghar Jafari (مطالعات روانشناختی, 2023)
The aim of this study was to investigate the mediating role of religious orientation in the relationship between cognitive emotion regulation strategies and corona anxiety. The research method was correlational. The statistical population of the study was the adults over 20 years old in Tehran. In this study, 480 participated in the research through an internet call with convenience sampling method. The instruments were Corona anxiety scale of Alipour, et al, emotion regulation questionnaire of Garnefski and Kraaij and religious orientation scale of Allport and Ross. Statistical analysis of data was performed using structural equation model. The results showed that there was negative correlation between adaptive of emotion regulation with corona anxiety and positive correlation between maladaptive of emotion regulation and corona anxiety. Also, cognitive emotion regulation had a significant relationship with corona anxiety both directly and indirectly through external and internal religious orientation. The indices also indicated the good fit of the model. Thus, the Corona anxiety of adolescents is influenced by emotion regulation and external and internal religious orientation. This finding can be used to design an intervention to reduce anxiety in the adults during the outbreak of infectious diseases.